Improving public works' value for money: a new procurement strategy. Issue 1 (6th May 2019) - Marinelli, Marina; Antoniou, Fani
Abstract : Purpose: The purpose of this paper is to propose a new procurement strategy with the aim to achieve higher value for money (VFM) in public works delivery. Its main innovation lies in the possibility of optional submission of cost-efficient design variants by any interested contractor within the context of an open procedure. The final scope of works incorporates the variants approved, and all contractors are invited to submit a bid for the revised scope and budget. Design/methodology/approach: This paper is a piece of applied research presenting the development of a new, cost-effective procurement strategy for public works, geared at the European Union (EU) legal framework. The strategy's feature compilation has been based on comprehensive literature review while numerical data from a real world project were used to demonstrate its financial advantages. Findings: The proposed strategy enables the delivery of the best value project at the lowest cost possible. This is achieved through ensuring high competition among competent contractors, improving the cost efficiency of technical solutions, discouraging future scope changes and establishing objectivity, fairness and transparency in the process of contract award. Practical implications: The use of the proposed strategy results in public projects of enhanced VFM, reduced constructability issues and less scope changes during the construction stage. Originality/value: The proposed strategy marks a new approach in procurement which enables the delivery of best VFM in public works. Therefore, it makes a valuable contribution towards the achievement of the overarching EU target for efficient public spending.